Disinfection by Ozone Microbubbles Can Cause Morphological Change of Fusarium oxysporum f. sp. melonis Spores - Tamaki, Masahiko; Kobayashi, Fumiyuki; Ikeura, Hiromi; Sato, Michio (The Plant Pathology Journal, 2018)
To investigate the difference in the disinfectant efficiency of ozone microbubbles (O MB) and ozone millibubbles (O MMB), the morphological change of the treated f. sp. spores was observed with scanning and transmission electron microscopies (SEM and TEM). The disinfectant efficiency of O MB on f. sp. spores was greater than that of O MMB. On observation with SEM, it was revealed that morphological change of f. sp. spores was caused by O MB and O MMB, and damage to the spore surfaces by O MB occurred sooner than that by O MMB. On observation with TEM, it was furthermore confirmed that f. sp. spores treated with O MB induced wavy deformation of cell membrane and the intracellular change different from that with O MMB. Therefore, the greater disinfection efficiency of O MB was suggested to be caused due to the function of the MB in addition to the oxidative power of O .